Adsorption of Remazol Blue And Indigosol Yellow Mixed Dyes Using Bidara Arab Leaves (Ziziphus spina-christi) - Kurnia, Mega; Suprapto, Suprapto; Ni'mah, Yatim Lailun (Universitas Islam Indonesia, 2024)
In this study, the adsorption of Remazol Blue and Indigosol Yellow using Bidara Arab leaves (Ziziphus spina-christi) as adsorbents was investigated through batch adsorption. The experimental parameters included contact time, adsorbent mass, initial concentrations, and pH. UV-Vis spectrophotometer was employed to measure the adsorption results at the maximum wavelength of each dye. The research was conducted in triplicate, and a t-test,